Local Computation of Maximal Independent Set - Ghaffari, Mohsen (Proceedings / annual Symposium on Foundations of Computer Science, 2022)
We present a randomized Local Computation Algorithm (LCA) with query complexity poly (Δ) · \log n for the Maximal Independent Set (MIS) problem. That is, the algorithm determines whether each node is in the computed MIS or not using poly (Δ)·\log n queries to the adjacency lists of the graph, with high probability, and this can be done for different nodes simultaneously and independently. Here Δ and n denote the maximum degree and the number of nodes. This algorithm resolves a key open problem in the study of local computations and sublinear algorithms (attributed to Rubinfeld).